Discovery of an orally bioavailable isoxazoline benzoxaborole (AN8030) as a long acting animal ectoparasiticide. Issue 23 (1st December 2015) - Zhang, Yong-Kang; Plattner, Jacob J.; Easom, Eric E.; Zhou, Yasheen; Akama, Tsutomu; Bu, Wei; White, W. Hunter; Defauw, Jean M.; Winkle, Joseph R.; Balko, Terry W.; Guo, Shenghai; Xue, Jian; et al.
Graphical abstract: A novel series of isoxazoline benzoxaborole small molecules was designed and synthesized for a structure–activity relationship (SAR) investigation to assess the ectoparasiticide activity against ticks and fleas. The study identified an orally bioavailable molecule, ( S )-3, 3-dimethyl-5-(5-(3, 4, 5-trichlorophenyl)-5-(trifluoromethyl)-4, 5-dihydroisoxazol-3-yl)benzo[ c ][1, 2]oxaborol-1(3 H )-ol (38, AN8030 ), which was long lasting in dogs ( t 1/2  = 22 days). Compound38 demonstrated 97.6% therapeutic effectiveness within 24 h of treatment, with residual efficacy of 95.3% against American dog ticks ( Dermacentor variabilis ) on day 30 and 100% against cat fleas ( Ctenocephalides felis ) on day 32 after a single oral dose at 50 mg/kg in dogs. Abstract: A novel series of isoxazoline benzoxaborole small molecules was designed and synthesized for a structure–activity relationship (SAR) investigation to assess the ectoparasiticide activity against ticks and fleas. The study identified an orally bioavailable molecule, ( S )-3, 3-dimethyl-5-(5-(3, 4, 5-trichlorophenyl)-5-(trifluoromethyl)-4, 5-dihydroisoxazol-3-yl)benzo[ c ][1, 2]oxaborol-1(3 H )-ol (38, AN8030 ), which was long lasting in dogs ( t 1/2  = 22 days). Compound38 demonstrated 97.6% therapeutic effectiveness within 24 h of treatment, with residual efficacy of 95.3% against American dog ticks ( Dermacentor variabilis ) on day 30% and 100% against cat fleas ( Ctenocephalides felis ) on day 32 after a single oral dose at 50 mg/kg in dogs.